2021
DOI: 10.1002/aet2.10706
|View full text |Cite
|
Sign up to set email alerts
|

Geographic mobility in the emergency medicine residency match and the influence of gender

Abstract: Objectives Women are underrepresented in emergency medicine (EM) leadership. Some evidence suggests that geographic mobility improves career advancement. We compared movement between medical school and residency by gender. Our hypothesis was that women move a shorter distance than men. Methods We collected National Residency Matching Program (NRMP) lists of ranked applicants from eight EM residency programs from the 2020 Main Residency Match. We added the gender expressed in interviews and left the Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…15 A separate analysis found that a majority of applicants remain within the same geographic region of their medical school for residency. 16 In addition to geography, other location factors considered by applicants include proximity to a partner or family, cost of living, preference for a particular size or type of community, and available recreational activities. 15,17 While the list of individual program features that influence applicants is extensive, some prominent characteristics include program length and reputation, number and type of training sites, patient population, interactions with residency and faculty, and opportunities to support subspecialty interests.…”
Section: How Do Applic Ants S Elec T P Otential Em Prog R Ams?mentioning
confidence: 99%
See 1 more Smart Citation
“…15 A separate analysis found that a majority of applicants remain within the same geographic region of their medical school for residency. 16 In addition to geography, other location factors considered by applicants include proximity to a partner or family, cost of living, preference for a particular size or type of community, and available recreational activities. 15,17 While the list of individual program features that influence applicants is extensive, some prominent characteristics include program length and reputation, number and type of training sites, patient population, interactions with residency and faculty, and opportunities to support subspecialty interests.…”
Section: How Do Applic Ants S Elec T P Otential Em Prog R Ams?mentioning
confidence: 99%
“…Most EM applicants, according to a survey of medical school graduates who participated in the 2020 Match, select residency programs based on combination of geography and program characteristics 15 . A separate analysis found that a majority of applicants remain within the same geographic region of their medical school for residency 16 . In addition to geography, other location factors considered by applicants include proximity to a partner or family, cost of living, preference for a particular size or type of community, and available recreational activities 15,17 .…”
Section: How Do Applicants Select Potential Em Programs?mentioning
confidence: 99%
“…However, available literature has primarily assessed Match results from the perspective of the EM residency applicant, including geographic mobility and the impact of the COVID-19 pandemic. [5][6][7] To date, no existing work describes the characteristics of EM residency programs that successfully fill their positions before the SOAP versus those that do not. Therefore, we sought to identify the risk of EM residency program characteristics including accreditation duration, primary clinical site ownership status, and geography pertaining to not filling positions before the SOAP.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the relationship between residency program–specific characteristics and their relation to Match results would provide important foundational data to the NRMP, the Accreditation Council for Graduate Medical Education (ACGME), EM residency program leadership, and potential EM residency applicants. However, available literature has primarily assessed Match results from the perspective of the EM residency applicant, including geographic mobility and the impact of the COVID‐19 pandemic 5–7 . To date, no existing work describes the characteristics of EM residency programs that successfully fill their positions before the SOAP versus those that do not.…”
Section: Introductionmentioning
confidence: 99%